Molecular modeling of transition metal and rare earth coordination compounds - Comba, Peter; Martin, Bodo (Advances in inorganic chemistry, 2019)
Various approaches of computational chemistry for the modeling of structures, electronic properties and reactivities of transition metal and rare earth metal complexes are discussed, including molecular mechanics (MM), ligand field theory (LFT), density functional theory (DFT) and ab initio quantum chemical methods. The discussion is based on three examples, i.e., the structure determination of an isomeric pair of hexamine cobalt(III) cage complexes with strikingly different electronic and electro-chemical properties and similar stabilities. It is shown that in this example, a simple and fast MM calculation in combination with ligand field theory (angular overlap model calculations, AOM) leads to an accurate result. The second example shows that for a thorough interpretation of the electronic and magnetic properties of a dysprosium(III) complex and its optimization as a single molecule magnet (SMM), ab initio quantum mechanics in combination with ligand field theory is the preferred approach. It is also shown how these results are validated with a ligand field theory based analysis of spectroscopic data. In the third example, the reactivity of high-valent iron oxidants is analyzed with DFT calculations, and it is shown that this type of analysis is more problematic than generally appreciated.